A low cost and portable single finger assistive device using air muscles. (1st January 2011) - Hurst, Thomas; Aw, K.C.
The paper shows the development of a low cost, lightweight and portable device to assist index finger movement for people with limited or no ability to use their hands. The mechanical system consists of a pair of air muscles connected to braided polymer cables applying force to the finger. The distal joints are actuated simultaneously by a single air muscle and rotational lever system while a second air muscle acts on the metacarpophalangeal (MCP) joints joint with a minor positive effect on the distal joints. The distal interphalangeal (DIP) and MCP joints are capable of achieving rotations up to 40° from resting and the proximal interphalangeal joint up to 65°. The device is capable of producing forces over 1 kg for a single finger. Force from the muscle itself increasing up to 3 kg at maximum contraction, producing a strong compliant force. Finger movement is similar to the curling motion of the human finger and can quickly and firmly grasp medium sized objects such as a plastic bottle of water.